2016
DOI: 10.1682/jrrd.2015.04.0057
|View full text |Cite
|
Sign up to set email alerts
|

Home-based hand rehabilitation after chronic stroke: Randomized, controlled single-blind trial comparing the MusicGlove with a conventional exercise program

Abstract: Abstract-Individuals with chronic stroke have limited options for hand rehabilitation at home. Here, we sought to determine the feasibility and efficacy of home-based MusicGlove therapy. Seventeen participants with moderate hand impairment in the chronic phase of stroke were randomized to 3 wk of home-based exercise with either the MusicGlove or conventional tabletop exercises. The primary outcome measure was the change in the Box and Blocks test score from baseline to 1 mo posttreatment. Both groups significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
146
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(151 citation statements)
references
References 71 publications
3
146
0
2
Order By: Relevance
“…As part of the research design, the current study limited therapy to 2 hours of therapy/day for 28 days, but greater gains may be possible with a longer duration of intensive therapy 37,38 , which may be pursued in future studies. An important finding is that subjects performed an average of 24,607 over 28 days, based on 879 arm repetitions each day, a value similar to the 466 movements/hour recorded in a prior study of one of the current input devices 27 .…”
Section: Discussionsupporting
confidence: 61%
“…As part of the research design, the current study limited therapy to 2 hours of therapy/day for 28 days, but greater gains may be possible with a longer duration of intensive therapy 37,38 , which may be pursued in future studies. An important finding is that subjects performed an average of 24,607 over 28 days, based on 879 arm repetitions each day, a value similar to the 466 movements/hour recorded in a prior study of one of the current input devices 27 .…”
Section: Discussionsupporting
confidence: 61%
“…Several studies have investigated self-directed [17], supervised [18] or self-administered [19][20][21][22] upper limb therapy on people with stroke [23][24][25]. The studies investigated several techniques including the use of novel robotic systems [26][27][28] to deliver rehabilitation therapies at home [29][30][31][32][33][34]. The results from most of these studies showed that stroke participants improved in several outcomes including ADL performance, which were maintained for several weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Studies outside rehabilitation have already shown that motivational interventions improve compliance with the therapy regimen [15], and recent home rehabilitation studies have emphasized the importance of motivational elements that would increase the duration and intensity of exercise [16, 17]. …”
Section: Introductionmentioning
confidence: 99%